Systemic Inequalities during COVID-19: A Result of American Neoliberal Society Gone Right - Vijayakumar, Mallika (Spectrum, 2021)
In this essay, I use Eric Cazdyn's article "Disaster, Crisis, Revolution" to reveal the ways in which COVID-19 is exacerbating inequalities in America. I explore how COVID-19 is strengthening racial and class inequalities to demonstrate that America's neoliberal healthcare system isn't failing these populations according to the way it was designed. I argue that by exposing these inequalities, the COVID-19 pandemic serves to reveal the dangers of neoliberalism: a system that cares only for the privileged.